Kajian Teknis Sistem Mine Dewatering dalam Upaya Pencegahan Genangan Air di Area Penambangan Pada Tambang Batubara Bawah Tanah Seam C2 Site Sapan Dalam PT Nusa Alam Lestari, Desa Salak, Kecamatan Talawi, Kota Sawahlunto - Nurdiani Fauziah; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2021)
At the research site, the problem that often occurs is the entry of water into the mining front. The water comes from ground water flowing through the fractures. Therefore, a mine drainage system is needed to support mining activities. At the mining site SD-C2 Lori 1 has 4 control tanks, where the pumping system is carried out by flowing water from the mining area to the control tank until the next control tank reaches the main sump. Based on data analysis, it can be concluded that the study site has an intensive fracture structure with a secondary permeability value of 10-2 with a free discharge classification. Groundwater discharge in all fractures is 10,32 m3/day. Based on the specifications of the existing pump, it should be able to compensate for the incoming water discharge, but because the head of the pump is greater than the maximum head of the pump in control tank 1 to control tank 2, the pump is unable to drain water properly until control tank 2. In addition, the number of control tanks with a total dimension of 9.5 m3 has not balanced the daily incoming water discharge with a total discharge of 10.32 m3/day, so it is recommended to add 1 control tank with dimensions of not less than 0.82 m3.